Osseous and Cartilaginous Trochlear Morphology in Pediatric Patients From 2 Months to 11 Years of Age: a Descriptive Analysis Based on Computed Tomography Scanning. Issue 5 (31st May 2022) - Ayala, Salvador; Rohde, Matt; Gupta, Anshal; Sanchez, Mark; Thomas, Nicholas; Tompkins, Marc; Parikh, Shital; Ellis, Henry; Green, Dan; Wilson, Phil; Shea, Kevin G.
Background: The anatomy of the trochlea plays a significant role in patella stability. Surgical approaches to alter the anatomy of the trochlea and associated structures to influence patella tracking continue to evolve. Unlike the development of the pediatric hip joint which has been well studies for decades, the developmental anatomy of the trochlea and its relationship to patella stability remains poorly understood. An improved understanding of trochlear growth and development may alter both the timing and type of surgical procedures for patella stability. Purpose: The purpose of this study was to describe the developmental changes of the osseous and cartilage trochlear morphology in skeletally immature specimens. Methods: Fifty-five skeletally immature cadaveric knees between the ages of 2 months and 11 years were evaluated using 0.625mm computed tomography scans. In the axial plane, measurements included medial and lateral osseous condylar height, medial and lateral cartilaginous condylar height, osseous and cartilaginous sulcus angles, osseous and cartilaginous condylar height asymmetry, and trochlear depth. Results: Analysis of trochlear morphology using osseous and cartilaginous measurements of condylar height, condylar height asymmetry, and trochlear depth demonstrated an increase in the size of the medial and lateral trochlea as age increased. The osseous and cartilaginous sulcus angles decreased (became deeper) with age until around age 8 and then plateaued. This corresponded with an increase in trochlear depth that plateaued also around age 8. In contrast, medial and lateral condylar height continued to increase through age 11. Cartilaginous condylar asymmetry rose slightly with age with the lateral condyle consistently larger than the medial condyle. Osseous condylar asymmetry increased with age but flipped from a larger medial condyle to a larger lateral condyle around age 8. Conclusions: This cadaveric analysis demonstrated that there is an increase in the medial and lateral trochlear height as age increased by all measurements analyzed. These changes in height continue to be seen through age 11 suggesting a still developing trochlea past this age. By age 8, a plateau in sulcus angle and sulcus depth suggests more proportionate growth after this point. Access to pediatric cadaveric specimens is exceptionally rare. This study provides a unique evaluate of the developing trochlea in young children, especially those under age 7, who rarely receive advanced imaging. Figure 1. The mean medial and lateral osseous trochlear height are identified with respect to age. Figure 2. The mean osseous and cartilaginous depth are identified with respect to age.